Fe3O4@SiO2 Magnetic Core-Shell Nanoparticles Functionalized with 1,4-dihydroxyanthraquinone as an Effective and Recyclable Adsorbent for Removal of Copper Ion from Aqueous Solutions - Majid Ghahraman Afshar; Mahsa Rajabi; Mahmood payehghadr; Niloufar Bahrami Panah (شیمی کاربردی روز)
In this research, Fe3O4@SiO2 magnetic core-shell nanoparticles functionalized with 1,4-dihydroxyanthraquinone molecules were synthesized and used to remove divalent copper ions from aqueous solutions. Then, the structural, crystalline, surface morphology, nanoparticle size, magnetic properties and thermal stability of synthetic nanoparticles were determined using Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscope, field emission scanning electron microscope, transmission electron microscope, vibrating sample magnetometer and thermal gravimetric analysis were investigated and identified. After the synthesis of magnetic nano adsorbent, the effect of different amount of adsorbent and study of absorption kinetics in the removal of divalent copper ions was investigated and the results showed that the use of 14 mg of adsorbent leads to the removal of copper ions with a maximum absorption of 96% at ambient temperature in a period of 28 minutes and at pH = 7. Finally, the recyclability and reusability of Fe3O4@SiO2-DAQ in the copper ion adsorption-desorption process was investigated using a magnetic magnet and the results confirm that this synthetic nanocomposite is an effective adsorbent with excellent performance to remove divalent copper ions.